Lipoblastic meningioma: case report - CARLOS GILBERTO CARLOTTI JUNIOR; BENEDICTO OSCAR COLLI; LEILA CHIMELLI; ANTONIO CARLOS DOS SANTOS; JORGE ELIAS JUNIOR (Arquivos de Neuro-Psiquiatria)
We describe the case of a patient presenting a right parietal mass lesion with an heterogeneous aspect on computed tomography, with hyperdense contrast uptake areas and hypodense areas with fat density. The unusual aspect of the lesion prevented preoperative and intraoperative diagnosis. The final histopathological examination revealed a meningothelial neoplasia with adipose differentiation, characterizing a lipoblastic meningioma.